PENGEMBANGAN LKPD BERBASIS AUDITORY, INTELLECTUALLY, REPETITION (AIR) PADA MATA PELAJARAN EKONOMI KELAS X SMA NEGERI 02 NEGARA BATIN - Elma Wati; Tiara Anggia Dewi (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2021)
Teaching materials have an important role in the learning process. However, the teaching materials used still do not meet the needs of students. The purpose of this research is to produce LKPD based Auditory, Intellectually, Repetition (AIR) products as valid and practical learning materials for BUMN, BUMD and BUMS. and standard eligibility criteria for learning media. This research is a type of development research using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The process to produce LKPD begins with a validation stage by media experts, design experts and material experts. Auditory, Intellectually, Repetition (AIR) based LKPD was also tested in schools to measure the response of class X students of SMA Negeri 02 Negara Batin. The results showed that this Auditory, Intellectually, Repetition (AIR) based LKPD was suitable for use in learning. This is indicated by the results of the final validation from design experts with a percentage of 80% with strong criteria, the results of the assessment by media experts with a percentage of 90% with very strong criteria, the results of the assessment by material experts with a percentage of 86.7% with very strong criteria and results. testing with a small group of 15 students with a percentage of 86.4% with very strong criteria. Based on the percentage obtained from an average expert validation of 89.2% with very strong criteria and student responses of 86.4% with very strong criteria, Auditory, Intellectually, Repetition (AIR) based LKPD is declared valid and practical to be used as references in the learning process.Keywords: Development,  LKPD, Learning Media